KARAKTERISASI PISANG HIBRID TETRAPLOID ‘GRNK’ HASIL PERSILANGAN PISANG TRIPLOID ‘GOROHO’ DENGAN PISANG IIAR DIPLOID MUSA ACUMINATA COLLA VAR. NAKAII NASUTION - Poerba, Yuyu S.; Martanti, Diyah; Handayani, Tri; Witjaksono, Witjaksono (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThe use of tetraploid banana in triploid banana breeding has been conducted through 4x x 2x crossing and/or its reciprocals, 2x x 4x crossing. However, the availability of tetraploid banana is naturally very limited, therefore artificially induced tetraploid banana is needed. The present research is aimed to generate tetraploid banana plants by crossing triploid banana ?Goroho? as female parent with wild diploid banana, Musa acuminata var. nakaii Nasution as male parent, and to characterize the tetraploid hybrid. 94 crossings were made by pollinating stigma of Pisang Goroho with polen of M. acuminata var. nakaii. Embrios resulted from hybridization were in vitro rescued and propagated. Hybrid plantlets were then acclimatized in the green house and seedlings were planted in the field for two cycles of banana reproduction. Ploidy identification, morphology and molecular characteristics were also conducted for two cycles of banana reproduction. Results of the experiment showed that 9 hybrid seeds were produced from 94 pollinations. However, only 2 hybrid embryos grew and developed into shoots and from two shoots only one shoot was survived. The one shoot were then in-vitro propagated to produce 21 hybrids planted in the field. After being evaluated for two plant reproductive cycles, all hybrid plants were tetraploids (2n=4x=44). The hybrid plants had drooping leaves, bigger fruit diameter compared to both parents, and blunt fruit tip. DNA (RAPD) profiles of tetraploid hybrid showed that 37.5% of the bands were from female parent, 37.5% from male parents, and 25% from both parents. The tetraploid hybrid ?GRNK? is expected to be useful in triploid banana breeding in the future.Key Words: Hybrid banana, tetraploid, Goroho, Musa acuminata Colla var. nakaii Nasution